Dysfunctions in the Recruitment and Selection Process in Contact Center - Bera, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article demonstrates possible alternatives of the progress in the recruitment and selection process in the contact center branch. The following publication also provides a critical view on the solutions applied. Additionally, it comprises a summary analysing types of dysfunctions possibly anticipating during the recruitment and selection process in the contact center branch.